A matter of style? Testing the moderating effect of driving styles on the relationship between job strain and work-related crashes of professional drivers. (July 2020) - Useche, Sergio A.; Cendales, Boris; Alonso, Francisco; Orozco-Fontalvo, Mauricio
Abstract: Different empirical studies suggest that both job strain and driving styles are significant contributors to the work-related traffic crashes suffered by professional drivers. Nevertheless, the current evidence falls considerably short when explaining why driving styles may modify (or not) the relationship between occupational stressors and professional drivers' safety outcomes. The aim of this study was to examine whether driving styles moderate the effect of job strain on professional drivers' Work Traffic Crashes (WTCs). This research was performed using the data collected from a sample of 753 professional drivers, responding to a self-report questionnaire on job strain (work stress indicator of the Job Demand-Control model), driving styles and work-traffic safety outcomes suffered in the past two years. Regression-based moderation analyses suggest that the job strain of professional drivers is positively associated with the occupational traffic crashes they suffer, and that such association is stronger in drivers with "reckless & careless", "anxious", and "angry & hostile" driving styles. Meanwhile, the "patient & careful" (positive) driving style was not associated with a lower risk of suffering a WTC, nor with a lower vulnerability to stress-related WTCs. The results of this study support the hypothesis that driving styles exert a statistical moderation between the job strain and the occupational traffic crashes suffered by professional drivers. These findings may support the design of evidence-based interventions in both the organizational and individual levels, focused stress-related factors and driving styles as predictors of work traffic crashes.